Analysis of Available Methods for Detecting Failures of Transmission Units During Operation - Abdullaev Shavkatbek Dadajon ugli; Toychiev Khasanboy Tokhir ugli (Zien Journals, 2022)
In this article, the concentration of abrasive particles accumulated in the crankcase of the transmission block under high ambient temperature conditions in the transmission blocks depends on the crankcase sealing and the recorded refueling frequency
Keywords: Transmission; operation; malfunctions; abrasive particles